Peningkatan Pengetahuan Siswa dalam Pemeliharaan Kesehatan Jantung Melalui Pendidikan Kesehatan dengan Tema Deteksi Dini Penyakit Infeksi Jantung di SMK Kesehatan Surya Global Cimahi - Budi Rustandi; Theophylia Melisa Manumara; Anggraeni Lestari; Dina Alipiya; Delia Ordora; Siti Jenab Andreani; Sarah Ayu Lestari; Reine Maharani Willyana; Muhammad Ferdiawan; Davina Apandi Putri; Dhea Lestari; Afifah Azahra; Novy Alawiyah; Fifih Fadya (Jurnal Medika: Medika, 2026)
Myocarditis is an inflammation of the heart muscle, usually caused by a viral infection, and can have serious consequences if not detected early. Early symptoms of myocarditis are often nonspecific and therefore often overlooked, especially in adolescents. Lack of knowledge about myocarditis is a factor in delayed treatment, potentially leading to cardiovascular complications. This activity aims to improve the knowledge of Surya Global Cimahi Health Vocational School students regarding the definition, risk factors, symptoms, prevention, and early detection of myocarditis through health education. The method used was a pre-experimental design with a one-group pre-test and discussion approach. The activity was conducted with 21 students. The pre-test was administered, the material was presented using visual lectures, leaflets, interactive discussions, and icebreakers, followed by an evaluation of understanding through discussion. The results showed an increase in student knowledge after the health education, indicated by an increase in the percentage of students in the "very good" knowledge category. Structured and interactive health education has proven effective in increasing students' understanding and awareness of myocarditis. This activity is expected to be a promotional and preventive effort in maintaining heart health from adolescence.